1953
DOI: 10.1161/01.cir.7.2.224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cortisone on the Size of Experimentally Produced Myocardial Infarcts

Abstract: In a total of 57 dogs the anterior descending branch of the left coronary artery was doubly ligated. Cortisone apparently (1) reduced the area of residual fibrosis; (2) All animals were sacrificed 14 to 22 days after operation.In group II (18 animals), the anterior descending branch of the left coronary artery was ligated 0.5 cm. below the origin of the circumflex branch (high ligation). Nine animals were treated with cortisone, 20 mg. twice a day for 20 days, and nine animals were kept as controls. All of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1955
1955
2003
2003

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(13 citation statements)
references
References 3 publications
2
10
0
Order By: Relevance
“…The epicardial ischemic area was reduced compared with postligation control (p < 0.05). Our results confirm previous reports that steroids permit an increase in coronary flow,26 27 perhaps by preventing the endothelial swelling associated with ischemia.2t 29 This increase in coronary flow and the increase in capillary oxygen tension without a corresponding increase in myocardial oxygen demand allow oxygen to diffuse farther into the ischemic zone. This was documented by an increase in the oxygen-diffusion zone (p < 0.001).…”
Section: Methodssupporting
confidence: 88%
“…The epicardial ischemic area was reduced compared with postligation control (p < 0.05). Our results confirm previous reports that steroids permit an increase in coronary flow,26 27 perhaps by preventing the endothelial swelling associated with ischemia.2t 29 This increase in coronary flow and the increase in capillary oxygen tension without a corresponding increase in myocardial oxygen demand allow oxygen to diffuse farther into the ischemic zone. This was documented by an increase in the oxygen-diffusion zone (p < 0.001).…”
Section: Methodssupporting
confidence: 88%
“…In addition, it has been demonstrated that interventions which may exert metabolic effects, such as glucose-insulin-potassium, act to protect ischemic myocardium from necrosis (4). The corticosteroid administration may have a beneficial effect on infarct size has been investigated by a number of workers, but the results have been conflicting (5)(6)(7). Since the newly developed methods for assessing myocardial ischemic injury are more sensitive and reliable than those previously available, we have undertaken to evaluate the effects of pharmacologic doses of corticosteroids on experimental infarcts.…”
mentioning
confidence: 99%
“…On the one hand, findings of Johnson et al [1953] and Shatney et al [1976] in coronaryligated dogs, and Lefer et al [1980] in cats, suggest a reduction of the infarct size by cor ticosteroids. On the other hand, such an ef fect was missing in the experiments of Opdyke et al [1953] and Vogel et al [1977], Although it is an indirect indication of the salvage of ischemic myocardium, the de crease of the infarct signs in the electrocar diogram obtained with corticosteroids in dogs [Libby et al, 1973], cats [Spath et al.…”
Section: Introductionmentioning
confidence: 99%